Development of Hydrogen Production Technology by Thermochemical Water Splitting IS Process Pilot Test Plan - TERADA, Atsuhiko; IWATSUKI, Jin; ISHIKURA, Shuichi; NOGUCHI, Hiroki; KUBO, Shinji; OKUDA, Hiroyuki; KASAHARA, Seiji; TANAKA, Nobuyuki; OTA, Hiroyuki; ONUKI, Kaoru; HINO, Ryutaro (Journal of Nuclear Science and Technology, 2007)
Japan Atomic Energy Agency (JAEA) has been conducting a study on a thermochemical IS process for hydrogen production. A pilot test of IS process is under planning that covers four R&D subjects: (1) construction of a pilot test plant made of industrial materials and completion of a hydrogen production test using electrically-heated helium gas as the process heat supplier, (2) development of an analytical code system, (3) component tests to assist the hydrogen production test and also to improve the process performance for the commercial plant, (4) a design study of HTTR-IS system. Development of innovative chemical reactors is in progress, which are equipped with a ceramic heat exchanger. In the design of the IS plant, it is important to establish the system for "design by analysis". Therefore, we have developed a multiphase flow analysis code that can analyze systems in which chemical reactions occur.